Fungal manipulation of hormone-regulated plant defense - Patkar, Rajesh N. (2018)
Fungi have adapted to diverse habitats and ecological niches, including the complex plant systems. Success of the pathogenic or symbiotic fungi in colonizing the plant tissue depends on their ability to modulate the host defense signaling [1]. Strategies that impart such abilities in fungi include the use of effector proteins that directly disrupt phytohormone-based defense signaling pathways and/or the deployment of mimics of specific plant molecules to evade recognition and the subsequent host immune response [1, 2]. Recent exciting findings have provided insight into a novel strategy whereby the fungal pathogens utilize the endogenous phytohormone-mimics and/or relevant metabolic enzymes to suppress host immunity. These studies strongly suggest that fungal metabolites, in addition to effector proteins, can chemically shape and maintain distinct pathogenic or symbiotic interkingdom relationships between plants and fungi.